-14+3n=4(n-3)

Simple and best practice solution for -14+3n=4(n-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+3n=4(n-3) equation:


Simplifying
-14 + 3n = 4(n + -3)

Reorder the terms:
-14 + 3n = 4(-3 + n)
-14 + 3n = (-3 * 4 + n * 4)
-14 + 3n = (-12 + 4n)

Solving
-14 + 3n = -12 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-14 + 3n + -4n = -12 + 4n + -4n

Combine like terms: 3n + -4n = -1n
-14 + -1n = -12 + 4n + -4n

Combine like terms: 4n + -4n = 0
-14 + -1n = -12 + 0
-14 + -1n = -12

Add '14' to each side of the equation.
-14 + 14 + -1n = -12 + 14

Combine like terms: -14 + 14 = 0
0 + -1n = -12 + 14
-1n = -12 + 14

Combine like terms: -12 + 14 = 2
-1n = 2

Divide each side by '-1'.
n = -2

Simplifying
n = -2

See similar equations:

| 2x-18=6(7-3x) | | 7+22x+3x^2=0 | | 12z-4=11z+4 | | -7x+7x=56 | | 8(1-3n)=-112 | | 9r(r+5)= | | 25q-(25q+40000)=0 | | 63x^4+126x^3+35x^2=0 | | 4+3n=20+7n | | =-0.3x^2+3x+4 | | 8x-(6-2x)=2x-6 | | G(x)=-0.3x^2+3x+4 | | m^2+4.5m-2.5=0 | | 7x+9=-103 | | 2x+11=65 | | xsquared-30x+50=0 | | 5i=4(5x-2u) | | 1-4x=-6x-17 | | 2=6y | | 18x-8=16x+8 | | (7v^2-4v-6)+(5v^2-3v+2)= | | 14x^4-6x^3+2x^2=0 | | 2xsquared+7=4x | | 8.35x+58.45=116.9 | | 2+7x=-159 | | 2squared+7=4x | | x+8-9=7 | | 2squad+7=4x | | -20+8a=4(8a+1) | | y=1.3x+7.7 | | 18x-8=8x+4 | | 4x^2=13x+35 |

Equations solver categories